Optimization of hydrophobic modification parameters of microporous polyvinylidene fluoride hollow-fiber membrane for biogas recovery from anaerobic membrane bioreactor effluent - Sethunga, Godakooru Sethunga Mudiyanselage Dilhara Prebhashwari (2020)
Tailoring the hydrophobic properties of membranes is an important requirement in gas-liquid membrane contactor processes because the membrane can be wetted by liquid. This paper describes the hydrophobic modification of the chemical surface of a polyvinylidene fluoride hollow-fiber membrane using a commercial perfluoropolyether, Fluorolink S10. The contact angle of the modified membrane was influenced by the modification parameters, and hence parameter optimization was required to obtain a highly hydrophobic membrane. The sodium hydroxide concentration (pH 8, 10 and 12), dehydrofluorination time (30, 60 and 90 min), and chemical solution grafting time (30, 60 and 90 min) were identified as the control parameters of this modification and were optimized using the Taguchi approach. The optimized membrane was then applied to recover methane from anaerobic membrane bioreactor effluent and benchmarked with a commercial polypropylene membrane manufactured for degasification of water. The contact angle of the polyvinylidene fluoride membrane was improved by 32% after the surface modification (under the optimal modification condition indicated by the Taguchi method). The membrane mass transfer coefficient was measured as 1.53 × 10−4 m/s. Our membrane showed better methane recovery performance than the commercial polypropylene membrane and a very stable flux without pore wetting during 10 days of operation with synthetic effluent (made by saturating a 60:40 methane/carbon dioxide mixture into tap water). In addition, the membrane prepared in this study could be operated without significant fouling (7% flux drop during 8 days of operation) with real anaerobic membrane bioreactor effluent.